Nutrigenomics-Associated Impacts of Nutrients on Genes and Enzymes With Special Consideration of Aromatase - Jenzer, Helena; Sadeghi-Reeves, Leila (Frontiers in Nutrition, 2020)
Interactions are occurring in the course of liberation, absorption, distribution, metabolism, and excretion of active ingredients, or at the target receptors. They are causing therapy failures and undesirable events. Forty-seven of fifty-seven human hepatic isoenzymes are specific and relevant in hormone and vitamin metabolism and biosynthesis. Aromatase (syn. CYP19A1) is one of the specific CYP450 isoenzymes so far not elucidated in detail. As aromatase-inhibiting phytochemicals are currently recommended for breast cancer prevention and as add-on accompanying aromatase-inhibitor pharmacotherapy, it was the aim of this literature review to assess whether a common interpretation on genetic and -omics basis could be found. Articles retrieved showed that traditional antioxidation diet is one of the most approved explanations of inhibition of aromatase by phytonutrients of flavonoid derivatives. Flavonoids compete for the oxygen provided by the heme moiety of aromatase in the course of aromatase-catalyzed conversion of steroid precursors to estrogens. Flavonoids are therefore promoted for breast cancer prevention. A further explanation of flavonoids' mechanism of action proposed was related to enzymatic histone deacetylation. By keeping DNA-structure wide through a high acetylation degree, acetylated histones favor transcription and replication. This mechanism corresponds to a procedure of switching genes on. Inhibiting acetylation and therefore switching genes off might be an important regulation of repressing cancer genes. Aromatase expression depends on the genotype and phenotype of a person. Aromatase itself depends on the expression of the heme moiety encoded in the genotype. Biosynthesis of porphyrins in turn depends on the substrates succinate and glycine, as well as on a series of further enzymes, with ALA synthetase as the rate-limiting step. The effect of the heme moiety as prosthetic group of aromatase further depends on the absorption of iron as a function of pH and redox state. To assess the function of aromatase precisely, multiple underlying biochemical pathways need to be evaluated. As a conclusion, the genetic regulation of metabolism is a complex procedure affecting multiple pathways. To understand a metabolic step, multiple underlying individually performing reactions need to be considered if personalized (nutritional) medicine should bring an advantage for a patient. Nutrition sciences need to consider the genome of an individual to truly find answers to nutrition-derived non-communicable diseases. With current GWAS (genome-wide association study) approaches, inherited errors of metabolism are identified and ideally treated effectively. It is much more difficult to get a precise genetic profile for non-communicable diseases stemming from multifactorial causes. Polygenic risks evaluation is feasible but diagnostic tools are not yet available in a desired extent. Neither flavonoid researchers nor providers of genetic testing kits are going into the details needed for a truly personalized nutritional medicine. The next step with profiling the exome and then the whole genome is on the threshold of becoming routine diagnosis and of bringing the desired details.